Engaging older adults in the process of aging research: a multimethod study evaluating the experience and efficacy of a citizen advisory group for a dementia risk reduction program - Danielle D’Amico; Marie Y. Savundranayagam; Rose Biles; Inbal Itzhak; Nicole D. Anderson; for the Canadian Consortium on Neurodegeneration in Aging (CCNA) CAN-THUMBS UP Study Group (Research Involvement and Engagement)
Abstract Background Collaborative research with end-users is an effective way to generate meaningful research applications and support greater impact on practice and knowledge exchange. To address these needs, a Citizen Advisory Group (CAG) of nine older adults (ages 64–80, 67% women) was formed to advise scientists on the development of Brain Health PRO (BHPro), a web-based platform designed to increase dementia prevention literacy and awareness. The current study evaluated if the CAG met its objectives, how inclusion of the CAG aligned with collaborative research approaches, and the CAG’s experience and satisfaction throughout the development process. Methods An anonymous online survey was administered to the CAG members and 30 scientist/trainee authors of the BHPro chapters. The CAG also participated in an online focus group. Results Most CAG members and chapter authors agreed that the CAG met its primary objectives and added unique value to BHPro. Both groups viewed the CAG’s involvement as well-aligned with engaged scholarship, co-production, integrated knowledge translation, and, to a lesser extent, participatory research practices. CAG members reported high satisfaction with personal goal attainment, which included learning, collaborating with others, and making a meaningful impact. Content analyses of the focus group revealed three categories: 1) personal benefits related to learning, connection, and feeling valued, 2) value of a masked peer-review process, and 3) an accessible final product. Conclusions Findings suggest that collaborating with end-users in the process of aging research confers personal and scientific benefits for both older adults and researchers.